Promoting hotel innovation with social media use - Garrido-Moreno, Aurora; García-Morales, Víctor J.; Lockett, Nigel (My University, 2022)
Service innovation has turned to be essential for hotels, to cope with current turbulent environment and quickly adapt to customers changing needs. To maintain competitiveness, hotels need to differentiate from competitors, improving existing services or offering new ones, creating memorable experiences for customers. To enhance innovation, hospitality firms are increasingly engaging customers in co-creation activities, to capture valuable knowledge, and crowdsource ideas. Additionally, absorptive capacity is emphasized as a significant antecedent of innovation activity in the tourism and hospitality industry. It is defined as the firm’s ability to identify, acquire, and use external knowledge to generate competitive products. Consequently, this organizational capability is emphasized as a key driver of service innovation. Moreover, today travel has become inherently technological, and tourism activity is powered by social media tools. These platforms facilitate connectivity, information sharing, and consumer generated content. The emergence of social media not only has transformed customer relations but is also changing internal firm processes such as innovation. However, despite the relevance of the topic, as tourism is one of the main economic activities in Spain, empirical evidence about the main antecedents of service innovation in hotels remain scarce. To extend knowledge on the issue, in the current study we empirically examine how social media use can foster service innovation, analysing also the role of customer co-creation and absorptive capacity in this phenomenon. Results confirm how service innovation has become a strategic priority for hotels to face current changing markets. Findings provide a holistic understanding of the chain of effects that leads to innovativeness when using social media, and offer relevant implications for academics and hotel managers.
Keywords: Hostelería; Service innovation; hotels; social media; co-creation with customers; absorptive capacity